t(5t+3)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

t=0

5t+3=0

Set the first factor equal to 0.

t=0

Set the next factor equal to 0.

5t+3=0

Subtract 3 from both sides of the equation.

5t=-3

Divide each term by 5 and simplify.

Divide each term in 5t=-3 by 5.

5t5=-35

Cancel the common factor of 5.

Cancel the common factor.

5t5=-35

Divide t by 1.

t=-35

t=-35

Move the negative in front of the fraction.

t=-35

t=-35

t=-35

The final solution is all the values that make t(5t+3)=0 true.

t=0,-35

The result can be shown in multiple forms.

Exact Form:

t=0,-35

Decimal Form:

t=0,-0.6

Solve for t t(5t+3)=0